Transparent lithium aluminosilicate glass ceramics

By optimizing the composition of the transparent lithium aluminosilicate glass-ceramic, the problem of reduced resistance to temperature changes and thermal expansion caused by the reduced lithium content is solved, and color perception distortion is reduced, making it suitable for use with various heating elements. High-performance results for cooking surfaces.

CN119330597APending Publication Date: 2025-01-21SCHOTT AG
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202410971550.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-19
Filing Date
2024-07-19
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the absence of the transparent lithium aluminosilicate glass ceramics, it is difficult to maintain sufficient temperature variability and low thermal expansion resistance while reducing the lithium content, and there is also the problem of color perception distortion.

Method used

By optimizing the composition of the glass ceramics, ensure that the SiO2 content is 62-70wt%, the Al2O3 content is 19-23wt%, the Li2O content is 2.4-3.4wt%, and the thermal expansion coefficient is controlled within the range of -0.8 to 1.5ppm/K, and the color Degree C* is less than 6, preferably less than 5.5.

Benefits of technology

It achieves high resistance to temperature changes and low thermal expansion while reducing lithium content, while reducing color perception distortion, and is suitable for cooking surfaces with various heating elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004953374610000031
    Figure BDA0004953374610000031
  • Figure BDA0004953374610000032
    Figure BDA0004953374610000032
  • Figure BDA0004953374610000111
    Figure BDA0004953374610000111
Patent Text Reader

Abstract

The invention relates to a transparent lithium aluminosilicate glass ceramic and to the use of the transparent lithium aluminosilicate glass ceramic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to transparent lithium aluminosilicate glass ceramics which are particularly suitable for use as cooking surfaces for cookware and to their use. Background Art

[0002] Glass ceramics, in particular transparent glass ceramics, have been known for many years. A variant of such glass ceramics known in the prior art is lithium aluminum silicate (LAS) glass ceramics, which have high quartz mixed crystals (HQMK) (in particular for transparent materials) or keatnetite mixed crystals (KMK) (in particular for translucent or opaque materials) as the main crystalline phase. In order to produce such glass ceramics, an initial glass, the so-called green glass, is first produced using a process that is relatively common in glass manufacturing. These green glasses are converted into glass ceramics by heat treatment (ceramicization). The transparent glass ceramics produced in this way can be used in different fields. In particular, such glass ceramics are used as cooking surfaces. In addition, such glass ceramics are also used as viewing windows for stoves and ovens, as worktops or safety glass.

[0003] The essential property of these materials for use as cooking surfaces is that they have a very low thermal expansion in the temperature range from room temperature to 700° C. This low thermal expansion in turn leads to a high resistance to temperature changes. The thermal expansion is adjusted by combining a crystalline phase with negative thermal expansion with an amorphous residual glass phase with positive thermal expansion. In the glass ceramics used to date, lithium oxide contents of more than 3.6 to 5.0 wt. % are usually used for this purpose.

[0004] Due to the rising raw material price of lithium, it is advantageous for economic reasons to reduce the lithium content in glass ceramics to a minimum. However, lithium is one of the three main components of lithium aluminosilicate glass ceramics and cannot be reduced at will. The Li2O content directly affects the core properties of the glass ceramic, such as viscosity in the melt and hot forming, which is important for manufacturability, or thermal expansion, which is important for use as a cooking surface.

[0005] Lithium price trends are not a new issue. Over the past 20 years, lithium prices have continued to rise. Despite this long-standing need, most commercially available glass-ceramics for cooking surfaces have about 3.8 wt% Li2O or more.

[0006] The following documents disclose glass ceramics with a Li2O content of less than 3.5 wt%: WO 2012 / 010341 A1, EP3502069A1, US2017050880, US2020189965, US2020140322, US2021387899, WO2021 / 224412A1. However, these glass ceramics have different disadvantages, for example, reduced resistance to temperature changes or poor solubility of green glass.

[0007] The applicant describes, for example, in DE 20 2022 106 826 U1, basic methods for producing lithium aluminum silicate glass ceramics even with low Li2O contents, which avoid the above-mentioned disadvantages. A method for producing transparent glass ceramics with low Li2O contents is also described therein.

[0008] In addition to the above-mentioned temperature stability, there are other special requirements for transparent glass ceramics. When using transparent glass ceramics as cooking surfaces, they are usually provided with a colored bottom coating so that the heating elements and the associated electronics arranged below the glass ceramic cannot be seen from above. In this case, it is usually required that the color perception of this bottom coating by the end user is not distorted by the glass ceramic. Similar requirements are imposed on the glass ceramic when using transparent glass ceramics as viewing windows, because in this case, color distortion must also be avoided when viewing through the viewing window.

[0009] Here, transparent glass ceramics generally refer to glass ceramics with low light scattering. The transmittance of such transparent glass ceramics can be adjusted within a wide range by means of absorption components (ie, coloring components). Summary of the invention

[0010] The object of the present invention is to provide a transparent lithium aluminum silicate glass ceramic which has a low cost but does not restrict its performance in use. In addition, the glass ceramic according to the invention should minimize the distortion of the color perception caused by the glass ceramic.

[0011] In particular, the glass ceramic should meet all requirements for use as a cooking surface with various heating elements. These include, in particular, radiation heating elements, induction heating elements and gas heating elements. This requires, in particular, a sufficiently high resistance to temperature changes and a high long-term heat resistance.

[0012] The solution of the present invention for achieving the above-mentioned object lies in the subject matter of the independent claim. Preferred embodiments and improved solutions are shown in the dependent claims.

[0013] The transparent lithium aluminum silicate glass ceramic according to the present invention has a thermal expansion coefficient of -0.8 to 1.5 ppm / K in the range of 20° C. to 700° C., a chromaticity C* of less than 6, preferably less than 5.5, based on a thickness of 4 mm, and a grain size of less than 80 nm in a high quartz mixed crystal phase. In this case, the glass ceramic contains the following components in the given contents (based on oxides, in wt %): SiO2 62–70 Al2O3 19–23

[0014] Furthermore, the glass ceramic does not contain Cr2O3, V2O5, MnO2 and MoO3 except for inevitable impurities.

[0015] Glass ceramics with a corresponding coefficient of thermal expansion have both a high resistance to temperature changes and a high long-term thermal stability. They are therefore suitable for use as cooking surfaces with various heating elements. The coefficient of expansion is at least -0.8 ppm / K. In this context, "ppm" means "parts per million", i.e. a relative dimensional change of 10 for a temperature change of 1 K. -6 Negative thermal expansion values ​​should be avoided. In the case of negative expansion (i.e. contraction), tensile stresses can develop in the surface of the glass ceramic during heating. At values ​​below -0.8 ppm / K, these stresses can reduce the mechanical strength of the cooking surface at the usual operating temperatures of the cooker. Thermal expansion rates of more than 1.5 ppm / K should also be avoided. Expansion rates of more than 1.5 ppm / K do not ensure that the glass ceramic has a sufficiently high resistance to temperature changes for use in cookers with radiant heating elements.

[0016] In one embodiment of the invention, the thermal expansion coefficient is at least -0.6 ppm / K, -0.4 ppm / K, -0.2 ppm / K, 0.0 ppm / K, 0.2 ppm / K, 0.4 ppm / K, 0.6 ppm / K or even 0.8 ppm / K. Furthermore, the thermal expansion coefficient is preferably at most 1.4 ppm / K, 1.3 ppm / K, 1.2 ppm / K, 1.1 ppm / K, 1.0 ppm / K, 0.8 ppm / K or even at most only 0.6 ppm / K.

[0017] In a preferred embodiment of the invention, the glass ceramic has a coefficient of thermal expansion of -0.8 to 0.8 ppm / K, preferably -0.5 to 0.5 ppm / K, particularly preferably -0.3 to 0.3 ppm / K. Such glass ceramics are particularly suitable for cooking surfaces in cookers with radiant or inductive heating elements.

[0018] With regard to the specific optical properties of the glass ceramic according to the invention in terms of transmittance and chromaticity, "based on a thickness of 4 mm" means that the corresponding properties are measured on a sample with a material thickness of 4 mm, or the corresponding properties are measured at different material thicknesses and converted to a material thickness of 4 mm.

[0019] Based on the L*a*b* color coordinates, the chromaticity C* is determined according to the following formula:

[0020] The color coordinates a* and b* are determined in a known manner from the transmission spectrum of the glass ceramic using the standard light of standard illuminant D65 and a 2° observer.

[0021] A chromaticity C* of less than 6, preferably less than 5.5, means that the color of the light changes only slightly when it passes through the glass ceramic. This is particularly important, for example, when using it as a cooking surface or fireplace viewing window.

[0022] The chromaticity of the glass ceramic is particularly evident, for example, when the glass ceramic is used as a cooking surface and is provided with a white or generally light-colored bottom coating. The thickness of the glass ceramic in these applications is generally 4 mm. Therefore, the light reflected by the coating on the back side travels a light path distance of 8 mm, so that the color shift caused by the inherent color of the glass ceramic has a greater influence than with a shorter light path distance. Therefore, for cooking surfaces or fireplace viewing windows with a white coating on the back side, a correspondingly low chromaticity is particularly advantageous. In this case, the chromaticity C* of the glass ceramic according to the invention is preferably less than 5.5, in particular less than 5.

[0023] The glass ceramic according to the invention has a grain size in the high quartz mixed crystal phase of less than 80 nm, preferably less than 70 nm, particularly preferably less than 60 nm, and particularly preferably less than 50 nm. The grain size has a direct influence on the optical properties of the glass ceramic. Excessively large grain sizes lead to increased light scattering in the glass ceramic, which manifests itself as turbidity in the glass ceramic.

[0024] The glass ceramics according to the present invention contain the following components (in wt%): SiO2 62–70, Al2O3 19–23 and Li2O 2.4–3.4.

[0025] In glass ceramics, SiO2 and Al2O3 together with Li2O components form the main components of the crystalline phase. At the same time, these components basically determine the glass-forming properties and the viscosity of green glass.

[0026] According to the SiO2 content in the glass ceramic of the present invention should not exceed 70wt%, because this component can significantly increase the viscosity of the glass, particularly the processing point. Higher SiO2 content is uneconomical for the good melting of glass and lower forming temperature. The extremely high SiO2 content exceeding 70wt% may lead to the formation of hot quartz in the ceramicization process. This move causes the thermal expansion coefficient to increase significantly and the optical properties of the material to deteriorate, especially in the form of turbidity. In this case, the minimum content of SiO2 should be 62wt%, because this is more favorable for the required characteristics (such as chemical resistance and heat resistance).

[0027] The glass ceramic preferably contains at least 63 wt % or even 64 wt % SiO2. The higher the SiO2 content in the glass ceramic, the better its heat resistance and chemical resistance. In addition, the glass ceramic preferably contains at most 69 wt %, at most 68 wt %, at most 67 wt %, at most 66 wt % or even only at most 65 wt % SiO2. The lower the SiO2 content in the glass ceramic, the better the meltability and processability of the green glass in hot forming.

[0028] The Al2O3 content of the glass ceramic according to the present invention is in the range of 19 to 23 wt%. Higher Al2O3 content may cause problems of devitrification and undesirable formation of mullite. Therefore, it should not exceed 23 wt%. Al2O3 content below 19 wt% is not conducive to the formation of high quartz mixed crystals and promotes the formation of undesirable crystalline phases. In addition, it has been shown that lower Al2O3 content also has an adverse effect on the chromaticity of the glass ceramic.

[0029] The glass ceramic preferably contains at least 20 wt % Al2O3. The higher the Al2O3 content in the glass ceramic, the better its heat resistance. In addition, the glass ceramic preferably contains at most 22 wt %, preferably at most 21.5 wt % Al2O3. The lower the Al2O3 content in the glass ceramic, the better the meltability and processability of the green glass in hot forming.

[0030] The Li2O content of the glass ceramic according to the invention is in the range of 2.4-3.4 wt %. It has been shown that with a Li2O content in this range, in combination with other components within the above-mentioned limits, glass ceramics with high resistance to temperature changes and good solubility can be produced. Li2O has a great influence on the thermal expansion of the glass ceramic, and therefore Li2O is selected in combination with other components of the glass ceramic according to the invention within the above-mentioned limits so that the resistance to temperature changes required by the invention can be achieved. In addition, a Li2O content of more than 2.4 wt % has a positive effect on the manufacturability of the glass ceramic, since this reduces the electrical resistance of the glass melt, reduces the viscosity and thus reduces the processing point. By reducing the viscosity of the glass melt, the efficiency of clarification can also be increased. Improved clarification helps to reduce production waste caused by the formation of bubbles in the green glass. In addition, Li2O also reduces the tendency of green glass to devitrify.

[0031] In a preferred embodiment, the glass-ceramic comprises at least 2.5 wt%, 2.6 wt% or even 2.7 wt% Li2O.

[0032] Lithium used to make glass-ceramics is usually derived from natural mineral sources such as spodumene or petalite, or alternatively from synthetically produced Li2CO3.

[0033] In a preferred embodiment, the glass ceramic contains high quartz mixed crystals as the main crystalline phase. "Main crystalline phase" means that the high quartz mixed crystals contained in the glass ceramic are higher in volume fraction than the keatnetite mixed crystals and other crystalline phases. In one embodiment of this embodiment, the glass ceramic contains <10 vol%, preferably <5 vol%, and particularly preferably <3 vol% of keatnetite mixed crystals. Wherein, vol% refers to the volume of the glass ceramic. The volume fraction is determined by means of the Rietveld analysis method based on the X-ray diffraction spectrum.

[0034] The coefficient of thermal expansion of keatite mixed crystals is usually higher than that of high quartz mixed crystals. Therefore, a low content of keatite mixed crystals and a high content of high quartz mixed crystals are particularly advantageous for reducing the coefficient of thermal expansion of glass ceramics. In addition, a low coefficient of thermal expansion also improves the resistance of glass ceramics to temperature changes. At the same time, keatite mixed crystals, due to their generally large crystal size, cause strong light scattering, so that an excessively high keatite content has an adverse effect on the optical properties of glass ceramics. In view of this, the content of keatite in the crystalline phase should also be kept as low as possible.

[0035] In addition to the above-mentioned SiO2, Al2O3 and Li2O contents, the glass ceramic according to the present invention also contains 0-1wt% Na2O. In this case, the 0-1wt% Na2O content in the glass ceramic according to the present invention will additionally improve the solubility and devitrification properties of the glass during molding. In addition, Na2O will also increase the electrical conductivity of the melt. This will help to couple energy through the electric heating device in the melting tank. However, its content will be limited because it will not be incorporated into the crystalline phase, but will basically remain in the residual glass phase of the glass ceramic. When the crystallizable initial glass is converted into glass ceramics, too high a content will impair the crystallization properties, especially affecting the rapid ceramicization speed. Thus, in the case of preferably rapid ceramicization, the grain size in the glass ceramic can be increased, which in turn will have an adverse effect on the scattering properties of the glass ceramic. In addition, a higher content will also have an adverse effect on the durability / heat resistance of the glass ceramic. Therefore, the glass ceramic preferably contains> 0.1-1wt% or 0.2-0.8wt% or even 0.3-0.6wt% Na2O.

[0036] Furthermore, the glass ceramic according to the invention further comprises 0-5 wt % ZnO, preferably 1.2-4.0 wt % ZnO, preferably 1.4-3.6 wt % ZnO, particularly preferably 1.4-3.0 wt % ZnO. As already mentioned above, Li2O contributes to reducing the coefficient of thermal expansion of the glass ceramic. Therefore, a reduction in the Li2O content, compared to the content usually used for transparent glass ceramics in the prior art, leads to a reduction in the coefficient of thermal expansion of the high quartz mixed crystals in the glass ceramic, so that the expansion coefficient required for use as a cooking surface may not be achieved. However, similar to Li2O, ZnO also contributes to reducing the coefficient of thermal expansion, so that the effect of the reduction in the Li2O content can be at least partially offset by adjusting the ZnO content.

[0037] In addition, ZnO also reduces the processing point and devitrification upper limit temperature of glass ceramics. However, too high ZnO content will increase the refractive index difference between the crystalline phase and the residual glass phase in the glass ceramics, causing the corresponding glass ceramics to scatter the incident light to a greater extent. Therefore, excessive increase in ZnO content will have an adverse effect on the transmittance and chromaticity of glass ceramics.

[0038] In addition to the above components, the glass ceramic according to the present invention also contains 1.5-2.5wt% TiO2. TiO2 plays an important role in nucleation together with ZrO2. The content of TiO2 is limited to a value of at most 2.5wt%, preferably at most 2.4wt%. A larger amount of TiO2 may cause devitrification during the hot forming process. In addition, it may also cause the refractive index of the residual glass phase to increase undesirably. At the same time, the glass ceramic contains at least 1.5wt%, preferably at least 1.6wt%, at least 1.7wt%, at least 1.8wt%, at least 1.9wt%, at least 2.0wt% or even at least 2.1wt% TiO2. The higher the content of TiO2, the faster the nucleation rate. This can shorten the ceramicization time of glass ceramics. Lower content helps to stabilize the ceramicization process and prevent accidental devitrification during the hot forming of green glass. In short, the content of TiO2 has an upper limit so as to keep the coloring effect of TiO2 on the optical properties of glass ceramics at a low level as much as possible. At the same time, however, the TiO2 content should not be too low in order to ensure sufficient nucleation and a short ceramization time.

[0039] In addition, the glass ceramic according to the present invention contains 1.5-2.5wt% ZrO2. In addition, ZrO2 is used as a nucleating agent in glass ceramics and can interact with other components of glass ceramics (such as SnO2 and TiO2). In this case, a ZrO2 content exceeding 1.5wt% is beneficial to improving nucleation. At the same time, it is advantageous to limit the content of ZrO2 to 2.5wt% because ZrO2 can deteriorate the melting properties of the batch. In addition, ZrO2 can also cause devitrification during hot forming. This may cause the undesirable formation of Zr-containing crystalline phases (such as baddeleyite). The glass ceramic preferably contains at least>1.6wt%, particularly preferably>1.7wt%, and especially preferably>1.8wt% ZrO2. In addition, the glass ceramic preferably contains at most 2.4wt%, 2.3wt%, 2.2wt%, 2.1wt%, 2.0wt% or even only at most 1.9wt% ZrO2. With these amounts, a particularly good balance can be achieved between a positive effect on nucleation and a still acceptable deterioration in solubility and hot forming. In this case, by optimizing the ZrO2 content, in particular with regard to the TiO2 content in the glass ceramic, a rapid ceramicization of green glass can also be achieved. The faster ceramicization with sufficient nucleation results in a smaller grain size in the glass ceramic, which in turn results in reduced light scattering. In addition, by using ZrO2, the content of TiO2 as a further nucleating agent can be reduced, thereby producing glass ceramics with reduced chromaticity.

[0040] Furthermore, the glass ceramic according to the invention contains 0-0.15 wt. % SnO2. SnO2 assists in the clarification of the green glass. Glass ceramics with the above-mentioned SnO2 contents are therefore characterized by particularly few defects due to the included bubbles. Furthermore, SnO2 can also be advantageously used in combination with other components of the glass ceramic according to the invention in order to ensure sufficient nucleation for the properties according to the invention.

[0041] However, this content should not exceed 0.15 wt%, because SnO2 will have an adverse effect on the optical properties of glass ceramics, and in particular may cause an increase in the chromaticity of glass ceramics. The reason is that SnO2 may form an additional absorption band for incident light together with TiO2, thereby causing a red shift in the transmitted light. In addition, a higher SnO2 content may also cause undesirable crystallization of Sn-containing crystalline phases (such as cassiterite) on the contact material (such as Pt / Rh) during the molding process, resulting in further deterioration of the optical properties of the glass ceramic. Therefore, it is particularly beneficial to limit the SnO2 content as much as possible for the optical properties of glass ceramics.

[0042] Therefore, according to another embodiment, it is provided that the transparent lithium aluminum silicate glass ceramic contains up to 0.13 wt % SnO 2, preferably up to 0.12 wt % SnO 2, preferably up to 0.11 wt % SnO 2. This can further reduce the negative influence of SnO 2 on the optical properties of the glass ceramic, while at the same time ensuring sufficient clarification of the green glass by the SnO 2 content.

[0043] In addition, except for inevitable impurities, the glass ceramics according to the present invention do not contain Cr2O3, V2O5, MnO2 and MoO3. V2O5 and MoO3 are generally used as the main colorants for coloring volume-colored glass ceramics, while Cr2O3 and MnO2 are generally used for auxiliary coloring. The above-mentioned colorants, especially V2O5, are usually very strongly colored in glass ceramics even if they are used in small amounts. Therefore, the content of the above-mentioned components in the glass ceramics according to the present invention should be kept as low as possible to ensure the chromaticity of the glass ceramics according to the present invention. In addition, these components exist as impurities in the raw materials or as components in the blank, which are added to the batch to improve the melting characteristics. In this case, "inevitable impurities" refers to the content of the corresponding components in the composition is less than 20ppm, particularly less than 10ppm, particularly less than 5ppm. In addition, except for inevitable impurities, the glass ceramics preferably do not contain Ce, Ni, Cu, Co, W and / or S or their oxides.

[0044] Furthermore, in one embodiment of the present invention, it is provided that the light transmittance τ of the transparent lithium aluminum silicate glass ceramic is based on a thickness of 4 mm. vis More than 80%.

[0045] Glass ceramics with a light transmittance of more than 80% relative to a thickness of 4 mm are particularly suitable for use as fireplace windows or heating panels. In fireplaces, this transmittance makes the fire particularly visible. In cookers, this transmittance makes, for example, luminous displays with a relatively low luminous density (such as LCD or OLED displays) particularly visible. In this case, the light transmittance τ of the glass ceramic according to the invention, based on a thickness of 4 mm, is 1.5 Å. vis Preferably it is greater than 82%, particularly preferably greater than 85%.

[0046] The above transmittance data for glass ceramics are related to a thickness of 4 mm and can be converted to other substrate thicknesses using the Lambert-Beer law. The transmittance τ was determined in the wavelength range of 380-780 nm using the light of the standard illuminant D65 and a 2° observer according to the preset values ​​of DIN 5033. vis This value is equivalent to the brightness Y in the CIExyY color space.

[0047] In order to assist the fining of green glass, in addition to the above-mentioned SnO2 content, a content of As2O3 and / or Sb2O3 of not more than 1.5 wt% has also been found to be advantageous in order to minimize the SnO2 content, since, as mentioned above, SnO2, in addition to its positive effect on the fining of green glass, can also have a negative effect on the optical properties of the glass ceramic. Here and hereinafter, "As2O3 and / or Sb2O3" means that the glass ceramic may contain these two components individually or simultaneously, wherein the two components can reach a content of not more than 1.5 wt% independently of each other.

[0048] Accordingly, according to another embodiment of the present invention, it is provided that, except for unavoidable impurities, the glass ceramic does not contain SnO2 and contains 0.5 wt% to 1.5 wt% of As2O3 and / or Sb2O3. This clarification is carried out completely without SnO2, and thus avoids the above-mentioned influence of SnO2 on the optical properties of the glass ceramic, and is particularly conducive to the production of transparent and color-neutral glass ceramics. Unlike SnO2, As2O3 and Sb2O3 do not affect the color of the glass ceramic, because their combination with TiO2 does not lead to enhanced coloring.

[0049] In summary, the glass ceramic can be refined accordingly by adding SnO 2 alone, by combining SnO 2 with As 2 O 3 and / or Sb 2 O 3 or by refining with the aid of As 2 O 3 and / or Sb 2 O 3 without SnO 2 .

[0050] In one embodiment of the present invention, the glass ceramic contains less than 0.05 wt% Fe2O3, preferably less than 0.04 wt% Fe2O3, particularly preferably less than 0.03 wt% Fe2O3, and especially preferably less than 0.02 wt% Fe2O3. Similar to V2O5, Cr2O3, MnO2 and MoO3, Fe2O3 also has a coloring effect in glass ceramics. In view of this, it is advantageous for transparent glass ceramics to limit the content of Fe2O3 to the above-mentioned values. For example, glass ceramics containing Fe2O3 as a colorant usually have a yellowing effect. For example, this may be the case with glass ceramics that contain both TiO2 and Fe2O3 introduced by impurities in the raw materials. This effect occurs in particular in glass ceramics that are clarified with the aid of SnO2, because SnO2 helps to increase the Fe content in Fe2O3. 2 + The content of TiO 2 in the glass ceramics is such that the coloring is enhanced by combining with TiO 2. If such glass ceramics are provided with a white bottom coating, for example, these bottom coatings have a clearly perceptible yellowish tint.

[0051] Furthermore, Fe2O3 influences the transmittance not only in the visible spectral range, but also in the near infrared range with a wavelength of about 3 μm. Thus, Fe2O3 not only influences the realizability of a certain color or the displayability of a color display. The absorption in the near infrared range determines how much heat energy the glass melt can absorb in the melting tank. It determines how much heat power of the radiant heating element can pass through the glass ceramic. Furthermore, this absorption determines whether and which infrared sensors can be used in the cooktop. Such sensors can be constructed, for example, as optical touch sensors or infrared receivers for wireless data transmission.

[0052] In this regard, it should be pointed out that in the present disclosure, the components of the glass are given in the form in which they are usually obtained by analysis. In this case, the components are usually given in a stable oxidation state (usually in the highest oxidation state). However, it should be pointed out that this does not necessarily correspond to the form in which the components actually exist.

[0053] For example, iron in oxide glass can exist in divalent and trivalent forms, namely as Fe 2+ or FeO or as Fe 3+ In the present disclosure, the data on the content of the respective component are related to the customary analytical data, however, it is obvious that this component may also be present in a form that deviates from the usually given "ideal" oxidation state.

[0054] Furthermore, in one embodiment of the invention, it is provided that the transparent lithium aluminum silicate glass ceramic contains 0.01-0.07 wt %, preferably 0.03-0.06 wt % Nd2O3. In this case, Nd2O3 helps to compensate for the color of the glass ceramic caused by SnO2, especially when refining with the aid of SnO2. In this case, in particular when the SnO2 content exceeds 0.1 wt %, the addition of Nd2O3 is advantageous for the production of a glass ceramic that is as color-neutral as possible.

[0055] In glass ceramics with Fe2O3 and TiO2 contents within the above limits, the addition of Nd2O3 also helps to reduce or eliminate the yellowing caused by Fe2O3 and TiO2, with only a slight effect on light transmittance. This effect is based on the narrow absorption band of Nd2O3 in the visible spectrum at wavelengths of 513, 526, 575, 585 and 745 nm and is particularly advantageous for the production of transparent, color-neutral glass ceramics.

[0056] In one embodiment of the present invention, the glass ceramic also contains less than 1wt% K2O. In glass ceramics, a K2O content of 0-<1wt% can improve the solubility and devitrification properties during the glass forming process. K2O can also additionally improve the conductivity of the melt. This helps to couple energy through the electric heating device in the melting tank. However, its content will be limited because it will not be incorporated into the crystalline phase, but will basically remain in the residual glass phase of the glass ceramic. When the crystallizable initial glass is converted into glass ceramics, too high a content will impair the crystallization performance, especially affect the rapid ceramicization speed. Similar to the above discussion on Na2O, too high a ceramicization speed and an increased grain size in the glass ceramic will also have an adverse effect on the scattering properties of the glass ceramic. In addition, a higher content will have an adverse effect on the durability / heat resistance of the glass ceramic.

[0057] If the K2O content in the glass ceramic is at most 0.8 wt%, 0.6 wt%, 0.5 wt%, 0.4 wt% or even 0.3 wt%, these properties can be further improved. In addition, in a special embodiment, the glass ceramic does not contain K2O except for unavoidable impurities.

[0058] In one embodiment of the invention, the glass ceramic contains less than 0.6 wt %, preferably less than 0.5 wt %, particularly preferably less than 0.4 wt % of MgO. MgO has a positive influence on the solubility and devitrification properties of the glass ceramic. In this case, limiting the MgO content to the above-mentioned limit values ​​helps to optimize the thermal expansion of the glass ceramic and reduce the color.

[0059] Furthermore, according to another embodiment of the invention, it is provided that the transparent lithium aluminum silicate glass ceramic contains less than 1 wt %, preferably less than 0.6 wt %, particularly preferably less than 0.5 wt % of CaO. CaO has a favorable effect on the devitrification properties of the glass ceramic. However, for colorless and transparent glass ceramics, it has proven to be advantageous to limit the CaO content to the above values, since CaO contributes to increasing the grain size of the glass ceramic. An increase in the grain size in turn leads to increased scattering, which results in a deterioration of the optical properties of the glass ceramic.

[0060] It has already been explained above that the ZnO contents described in the glass ceramic according to the invention lead to increased scattering, since too high a ZnO content leads to an increased difference in refractive index between the crystalline phase and the residual glass phase in the glass ceramic. In order to counteract this effect, according to a further embodiment, the glass ceramic preferably also contains more than 1.8 wt %, preferably more than 2.5 wt %, particularly preferably more than 2.8 wt % of BaO. An increased BaO content reduces the tendency of the glass ceramic to scatter incident light, since the addition of BaO can match the refractive index of the residual glass phase to the refractive index of the crystalline phase of the glass ceramic at the same grain size. This effect occurs in particular in the case of Li2O and ZnO contents within the above-mentioned limits, when the SrO and CaO contents in the glass ceramic are simultaneously low.

[0061] In addition, similar to Li2O, BaO also causes a decrease in the viscosity of the glass melt, thereby causing a decrease in the processing point. In order to improve the solubility of the green glass, it is advantageous that, in combination with the above-mentioned Li2O content, the glass ceramic contains more than 2.6 wt%, more than 2.7 wt%, more than 2.8 wt%, more than 2.9 wt% or even more than 3.0 wt% of BaO. In the glass ceramic, BaO also plays an important role in improving the devitrification performance of the green glass during the hot forming process.

[0062] Yet, facts show that, during ceramization, BaO can have a negative impact on the formation of crystalline phase.Therefore, in order to avoid needing longer ceramization time, the content of BaO is preferably limited to maximum 5.0wt%, 4.5wt%, 4.0wt%, 3.9wt%, 3.8wt%, 3.7wt%, 3.6wt% or even 3.5wt%.

[0063] According to another embodiment of the present invention, the ratio of Al2O3 to TiO2 is in the range of 7 to 12, preferably in the range of 8 to 11, and particularly preferably in the range of 8.5 to 10.5. It has been shown that the ratio of Al2O3 to TiO2 in this range has a particularly favorable effect on the color of the glass ceramic and at the same time enables particularly stable ceramicization.

[0064] In one embodiment of the present invention, the glass ceramic comprises the following components (based on oxides, wt %):

[0065] Except for inevitable impurities, the glass ceramic does not contain Cr2O3, V2O5, MnO2 and MoO3.

[0066] Furthermore, such glass ceramics may also contain SrO, wherein the SrO content mainly comes from impurities in the raw materials used to produce the glass ceramic. Among other things, SrO contributes to the scattering of light by the glass ceramic. Therefore, it is advantageous to keep the SrO content in the glass ceramic as low as possible.

[0067] The following table contains three further embodiments of the composition of the glass ceramic according to the invention comprising the following components (based on oxides, in wt %): Preferred Particularly preferred The most preferred <![CDATA[Si2O]]> 63–70 64–70 65–70 <![CDATA[Al2O3]]> 19–23 19–22.5 19–22 <![CDATA[Li2O]]> 2.5–3.4 2.7–3.4 2.9–3.4 <![CDATA[Na2O]]> 0.1–0.8 0.3–0.7 0.4–0.6 <![CDATA[K2O]]> <0.8 <0.5 <0.3 MgO 0–0.6 0.1–0.5 0.1–0.4 CaO <0.7 <0.4 <0.1 BaO 1.8–3.0 1.8–2.5 1.8–2.0 ZnO 1–3 1.2–2.5 1.3–2.2 <![CDATA[TiO2]]> 2.0–2.5 2.1–2.4 2.2–2.4 <![CDATA[ZrO2]]> 1.6–2.0 1.7–2.0 1.7–1.9 <![CDATA[SnO2]]> 0–0.15 0–0.13 0.03–0.13 <![CDATA[Nd2O3]]> 0–0.15 0–0.1 0-0.07

[0068] In this case, apart from unavoidable impurities, the glass ceramic does not contain Cr2O3, V2O5, MnO2 and MoO3.

[0069] Furthermore, apart from unavoidable impurities, the glass ceramic can be free of K2O, As2O3 and Sb2O3.

[0070] Three alternative embodiments of the composition of the glass ceramic according to the present invention comprise the following components (based on oxides, in wt %):

[0071] Except for inevitable impurities, the glass ceramic does not contain Cr2O3, V2O5, MnO2 and MoO3.

[0072] Furthermore, apart from unavoidable impurities, the glass ceramic can be free of K2O, As2O3 and Sb2O3.

[0073] Three other embodiments of the composition of the glass ceramic according to the invention comprise the following components (in wt % based on oxides):

[0074] Except for inevitable impurities, the glass ceramic does not contain Cr2O3, V2O5, MnO2 and MoO3.

[0075] In these embodiments, the fining of the green glass based on the above composition can be achieved by means of SnO2, by means of a combination of SnO2 and As2O3 and / or Sb2O3, or by means of As2O3 and / or Sb2O3 alone (i.e. without using SnO2). The content of each component in the composition can adopt the above limit values.

[0076] Three other embodiments of the composition of the glass ceramic according to the invention comprise the following components (in wt % based on oxides): Preferred Particularly preferred The most preferred <![CDATA[Si2O]]> 63–69 64–68 65–67 <![CDATA[Al2O3]]> 19–22 20–22 21–22 <![CDATA[Li2O]]> 2.5–3.4 2.8–3.4 3.1–3.4 <![CDATA[Na2O]]> 0.1–0.8 0.3–0.8 0.5–0.7 <![CDATA[K2O]]> 0–0.6 0–0.4 0–0.2 MgO 0–0.6 0.1–0.5 0.3–0.5 CaO 0.1–0.8 0.2–0.7 0.3–0.5 BaO 0.2–1.5 0.4–1.2 0.7–1.1 ZnO 1.1–3.0 1.4–2.5 1.7–2.1 <![CDATA[TiO2]]> 2.0–2.4 2.1–2.3 2.1–2.3 <![CDATA[ZrO2]]> 1.6–2.0 1.7–2.0 1.8–2.0 <![CDATA[SnO2]]> 0–0.15 0.05–0.15 0.1–0.15 <![CDATA[Nd2O3]]> 0–0.07 0.01–0.07 0.02–0.07

[0077] Apart from unavoidable impurities, the glass ceramic may in particular be free of As2O3 and Sb2O3.

[0078] Three other embodiments of the composition of the glass ceramic according to the invention comprise the following components (in wt % based on oxides):

[0079] In this case, the glass ceramic does not contain Cr2O3, V2O5, MnO2 and MoO3 except for unavoidable impurities.

[0080] Furthermore, apart from unavoidable impurities, the glass ceramic can be free of As2O3 and Sb2O3.

[0081] The glass ceramics according to the invention are used as cooking surfaces, fireplace windows, grilling or frying surfaces, covers for fuel elements in gas grills, oven windows, in particular oven windows for pyrolysis ovens, work surfaces or tabletops in kitchens or laboratories, covers for lighting devices, in fire-resistant sealing glasses and as safety glass, optionally in laminated composites, as carrier plates or oven linings in thermal processes or as back covers for mobile electronic devices.

[0082] The glass ceramic according to the invention can be used in particular as a cooking surface. This cooking surface can be provided completely or partially with a decorative or functional coating on the top and / or bottom. A touch sensor for operating the cooking surface can also be provided on the bottom. This can be, for example, a capacitive sensor that is embossed, glued or pressed.

[0083] The present invention will be further described below in conjunction with the embodiments. DETAILED DESCRIPTION

[0084] The crystallizable green glass in the example is melted from a technical batch raw material commonly used in the glass industry at a temperature of 1620° C. to 1680° C. for 4 hours. The requirements for economical raw materials and low impurity content of undesirable impurities can be reconciled by selecting this raw material. After the mixture is melted in a crucible made of sintered quartz glass, the melt is transferred to a Pt / Rh crucible with an inner crucible made of quartz glass and homogenized by stirring at a temperature of 1600° C. to 1640° C. for 60 minutes. After homogenization, the glass is clarified at a temperature of 1640° C. to 1680° C. for 3 to 3.5 hours. Subsequently, a glass of approximately 120×120×30 mm is cast. 3 The blocks are then cooled in an annealing furnace starting from 650-680°C at 30 K / h to room temperature, depending on the viscosity of the glass, in order to relieve stress. These castings are divided into the required sizes for testing and ceramicization.

[0085] The green glass sample was ceramized by means of a ceramization process having the following steps: a) Heating from room temperature to 740°C within 25 minutes, b) maintained at 740°C for 20 minutes, c) increasing the temperature from 740°C to 780°C within 6.5 minutes, d) Raise the temperature from 780°C to 825°C within 20 minutes, e) increasing the temperature from 825°C to 910°C within 8.5 minutes, f) maintaining the temperature at 910°C for 10 minutes, g) Cool to room temperature over 125 minutes.

[0086] This ceramization process can be considered as exemplary. The properties of the glass-ceramic can be fine-tuned by varying the temperature and holding time of the individual steps or by adding other steps (eg additional holding time).

[0087] For example, the following parameters can also be used for ceramicization: a) heating from room temperature to 680°C to 760°C within 3 to 60 minutes, b) heating the crystallizable green glass to a nucleation temperature range T for a period of 10 to 100 minutes a to 800°C, c) heating the glass containing the crystal nuclei to a temperature range of 810° C. to 930° C. with a high crystal growth rate within 5 to 80 minutes, d) maintaining the temperature at 810° C. to 930° C. for 2 to 60 minutes, e) Cool to room temperature in less than 150 minutes.

[0088] The following table contains compositions and material properties of examples according to the present invention.

[0089] In this case, the coefficient of thermal expansion CTE is determined by means of a method which is essentially based on DIN ISO 7991 from 1998.

[0090] To measure the upper devitrification temperature (OEG), green glass is melted in a Pt / Rh 10 crucible. The crucible is then kept for 5 hours at different temperatures within the processing temperature range. The upper temperature at which the first crystals appear at the contact surface between the glass melt and the crucible wall determines the OEG value.

[0091] The processing point (T4) of the green glass was determined in accordance with DIN ISO 7884-2 using a stirred viscometer.

[0092] When converting green glass into glass ceramic, the density increases, since the density of the crystalline phase is higher than that of the amorphous glass. The so-called shrinkage represents the linear length change during the conversion of green glass into glass ceramic. This shrinkage is calculated (in percent) from the density of the green glass and the density of the glass ceramic using the following formula:

[0093] Among them, T g Indicates the transition temperature of green glass, also known as the glass transition temperature. This transition temperature is determined by dilatometry.

[0094] The transmittance τ is determined in the wavelength range 380-780 nm using the light of the standard illuminant D65 and a 2° observer according to the preset values ​​of DIN 5033. vis This value is equivalent to the brightness Y in the CIExyY color space. This value is a measure of the human eye's perception of brightness.

[0095] The transmission spectra were determined according to ISO 15368: 2021. Table 2 exemplarily contains the spectral transmittances "T@..." for wavelengths of 470 nm, 600 nm, 630 nm, 700 nm, 950 nm and 1600 nm.

[0096] The color coordinates in the CIExyY color space and in the CIELab color space were determined in transmission using a 2° observer and the light of standard illuminant D65 according to the specifications of CIE 1932.

[0097] All transmittance measurements were performed on samples with a thickness of 4 mm and smoothed on both sides.

[0098] The volume fraction “HQMK phase content” and the grain size of the crystalline phase “HQMK grain size” were determined from the X-ray diffraction spectrum by means of Rietveld analysis.

[0099] Table 1: Compositions of exemplary glass-ceramics, in wt% based on oxides: Table 1 Table 1 Table 1 Table 2: Material properties of exemplary glass-ceramics Table 2 Table 2 Example 13 14 15 16 17 18 <![CDATA[T g ]]> ℃ 689 683 681 690 695 697 Glass density <![CDATA[g / cm 3 ]]> 2.5036 2.5124 2.5199 2.4605 2.4631 2.5106 HQMK phase content Vol.-% 61 60 61 66 64 58 HQMK grain size nm 36 45 53 43 43 39 Density of glass ceramics g / cm3 2.5820 2.5780 2.5859 2.5461 2.5518 2.5893 Shrinkage % 1.023 0.856 0.858 1.133 1.172 1.024 CTE(20;700℃) ppm / K -0.26 0.10 0.11 -0.19 -0.06 -0.10 <![CDATA[τ vis ]]> % 85.9 86.3 88.7 85.4 84.6 86.8 L* 94.3 94.4 95.5 94.0 93.7 94.7 a* -0.3 0.1 -0.3 0.0 0.0 -0.3 b* 4.9 3.8 3.2 3.2 3.2 4.2 C* 4.9 3.8 3.2 3.2 3.2 4.2 T@400nm % 67.0 74.4 77.0 72.9 72.5 69.8 T@470nm % 81.2 82.4 85.6 82.4 81.5 82.9 T@600nm % 87.6 87.9 89.8 87.1 86.4 88.4 T@630nm % 88.3 88.7 90.3 88.6 88.1 88.9 T@700nm % 89.5 89.7 90.7 89.7 89.2 89.9 T@950nm % 89.9 89.8 90.1 89.9 89.6 90.0 T@1600nm % 89.1 89.5 89.8 88.7 88.7 89.6 Table 2 Example 19 20 21 22 <![CDATA[T g ]]> ℃ 682 692 Glass density <![CDATA[g / cm 3 ]]> 2.5133 2.5165 HQMK phase content Vol.-% 61 61 60 62 HQMK grain size nm 44 43 40 40 Density of glass ceramics g / cm3 2.5795 2.5943 Shrinkage % 0.863 1.010 CTE(20;700℃) ppm / K 0.11 0.22 <![CDATA[τ vis ]]> % 84.9 85.1 85.5 84.7 L* 93.8 93.9 94.1 93.8 a* -0.2 0.0 0.0 -0.1 b* 3.7 4.1 4.0 4.6 C* 3.7 4.1 4.0 4.6 T@400nm % 69.3 71.7 72.9 69.2 T@470nm % 81.5 81.0 81.4 80.2 T@600nm % 86.8 86.8 87.1 86.5 T@630nm % 88.5 87.6 87.8 87.3 T@700nm % 89.6 88.7 88.9 88.6 T@950nm % 89.9 89.8 89.9 89.6 T@1600nm % 89.6 89.0 89.2 89.2 .

Claims

1. A transparent lithium aluminosilicate glass ceramic having a thermal expansion coefficient of -0.8 to 1.5 ppm / K in the range of 20° C. to 700° C., The glass ceramic has a chromaticity C* of less than 6 based on a thickness of 4 mm, a grain size of less than 80 nm in a high quartz mixed crystal phase, and comprises the following components based on oxides in wt %: And wherein except inevitable impurities, the glass ceramic does not contain Cr2O3, V2O5, MnO2 and MoO3.

2. The transparent lithium aluminum silicate glass ceramic according to claim 1, characterized in that Based on a thickness of 4 mm, the light transmittance τ of the transparent lithium aluminum silicate glass ceramic is vis Greater than 80%.

3. The transparent lithium aluminum silicate glass ceramic according to any one of claims 1 or 2, characterized in that The transparent lithium aluminosilicate glass ceramic contains at most 0.13 wt %, preferably at most 0.12 wt %, particularly preferably at most 0.11 wt % SnO 2 .

4. The transparent lithium aluminosilicate glass ceramic according to any one of the preceding claims, characterized in that Except for unavoidable impurities, the transparent lithium aluminosilicate glass ceramic contains no SnO 2 and contains 0.5 wt % to 1.5 wt % of As 2 O 3 and / or Sb 2 O 3 .

5. The transparent lithium aluminosilicate glass ceramic according to any one of the preceding claims, characterized in that The transparent lithium aluminosilicate glass ceramic contains less than 0.05 wt %, preferably less than 0.04 wt %, particularly preferably less than 0.03 wt %, and especially preferably less than 0.02 wt % of Fe 2 O 3 .

6. The transparent lithium aluminosilicate glass ceramic according to any one of the preceding claims, characterized in that The transparent lithium aluminosilicate glass ceramic contains 0.01-0.07 wt % of Nd2O3.

7. The transparent lithium aluminosilicate glass ceramic according to any one of the preceding claims, characterized in that The transparent lithium aluminosilicate glass ceramic contains less than 1 wt %, preferably less than 0.7 wt %, particularly preferably less than 0.5 wt %, and especially preferably less than 0.3 wt % of K 2 O.

8. The transparent lithium aluminosilicate glass ceramic according to any one of the preceding claims, characterized in that The transparent lithium aluminosilicate glass ceramic contains less than 0.6 wt %, preferably less than 0.5 wt %, particularly preferably less than 0.4 wt % of MgO.

9. The transparent lithium aluminosilicate glass ceramic according to any one of the preceding claims, characterized in that The transparent lithium aluminosilicate glass ceramic contains less than 1.0 wt %, preferably less than 0.6 wt %, particularly preferably less than 0.5 wt % of CaO.

10. The transparent lithium aluminosilicate glass ceramic according to any one of the preceding claims, characterized in that The transparent lithium aluminosilicate glass ceramic contains more than 1.8 wt %, preferably more than 2.5 wt %, particularly preferably more than 2.8 wt % of BaO.

11. The transparent lithium aluminosilicate glass ceramic according to any one of the preceding claims, characterized in that The ratio of Al2O3 to TiO2 is in the range of 7 to 12, preferably in the range of 8 to 11, particularly preferably in the range of 8.5 to 10.

5.

12. The transparent lithium aluminosilicate glass ceramic according to any one of the preceding claims, characterized in that The glass ceramic contains the following components based on oxides in wt %: And wherein except inevitable impurities, the glass ceramic does not contain Cr2O3, V2O5, MnO2 and MoO3.

13. Use of the glass ceramic according to any of the preceding claims as a cooking surface, a fireplace viewing window, a grilling or frying surface, a cover for a fuel element in a gas grill, an oven viewing window, in particular an oven viewing window for a pyrolysis oven, a work surface or tabletop in a kitchen or laboratory, a cover for a lighting device, in fire-resistant sealing glass and as safety glass, optionally in a laminated composite, as a carrier plate or furnace lining in thermal processes or as a back cover for mobile electronic devices.

Citation Information

Patent Citations

  • Lithium aluminum silicate glass ceramic

    DE202022106826U1

  • Glass ceramic with reduced lithium content

    EP3502069A1

  • Partially crystallised glass plate

    US20170050880A1

  • Beta-quartz glass-ceramics with high zinc content

    US20200140322A1

  • Transparent beta-quartz glass-ceramics with low lithium content

    US20200189965A1